Analysis of Road Performance and Vehicle Parking Characteristics in the Halim Perdanakusuma International Airport Area - Andri Irfan Rifai; Khairul Hafis (Journal of World Conference (JWC), 2021)
The Corona virus that broke out around the Wuhan area in December has spread in 100 countries and caused more than 100,000 people worldwide to test positive for infection. The impact of this pandemic has caused countries to close access in and out to their respective countries, including Indonesia, which has caused threats to the economy, especially in the aviation sector. The aviation sector which was affected by the Covid-19 epidemic affected all sectors in it including airport operations, namely the parking revenue sector. The decrease in the number of aircraft use has an impact on the number of vehicles entering and exiting which results in a significant decrease in the parking revenue itself. Therefore, the purpose of this study is to determine the performance of roads and vehicle parking characteristics. The method used in this research is to conduct direct field surveys including parking accumulation, parking duration, parking lot capacity, road geometry, traffic volume, side friction and vehicle speed. The analysis results obtained that the parking characteristics for the highest accumulation of four-wheeled vehicles are 1038 vehicles and 329 vehicles for two-wheeled vehicles, parking duration ranges from <1 hour for cars and> 7 hours for motorbikes, the highest parking volume is 3578 cars and 1180 motorbikes, turnover rate parking lots on average 0.14 cars / plot and 0.04 motorbikes / parking lot. The average car index is 82.9% and 33.1% for motorbikes, so that vehicle parking at the airport still accommodates parking demand. The impact of the Covid-19 pandemic caused a decrease in vehicle volume by 91% for four-wheeled vehicles and 55.4% for two-wheeled vehicles. In terms of parking characteristics, vehicle parking at Halim Perdanakusuma International Airport can still accommodate requests. For the performance of the Angkas I Halim Perdanakusuma road section.